Analisis Kualitas Pelayanan Terhadap Kepuasan Masyarakat dengan Metode Service quality dan Metode Importance perfomance analysis Pada Kantor Kelurahan Berbek Kabupaten Sidoarjo - Anum Umar Fanany; Suhartini Suhartini; Gatot Basuki H.M (Prosiding SENASTITAN: Seminar Nasional Teknologi Industri Berkelanjutan, 2023)
Kelurahan is an administrative area under a sub-district composed of several community units (RW) and is led by the village head. To provide the best service for the community, the Kelurahan Office needs to know the extent of the quality of service that has been carried out so that it can seek improvements that follow the demands and assessments of the community. This study discusses the measurement of community satisfaction in service quality at the Kelurahan Office using the Service quality (SERVQUAL) and Importance Performance Analysis (IPA) methods to measure the level of satisfaction and service quality provided. This study aims to determine the level of community satisfaction with the services of the sub-district office, which will later become the basis for improving the service quality. Based on the results of the study indicate that the quality of service at the Berbek Sub-District Office, Sidoarjo Regency needs to re-evaluate the performance of the services provided to meet the community's expectations.